Economic, Social, and Environmental Aspects of Ocean Current Turbine Installations in the Indonesian Strait (Collaborate Engineering Daily Book Series, 2025)
The development of tidal current power plants in Indonesia's straits not only considers technical aspects but also carries significant implications from economic, social, and environmental perspectives. From an economic standpoint, the initial investment for installing tidal current turbines is relatively high, particularly regarding foundational construction, submarine cable installation, and supporting infrastructure. Nevertheless, the potential for stable and sustainable energy can yield long-term benefits by reducing dependence on fossil fuels and enhancing energy security across the archipelago. Furthermore, this project has the potential to stimulate local economic growth through job creation at the construction, operational, and maintenance stages. From a social perspective, the development of tidal current turbines must take into account interactions with coastal communities, particularly fishermen and shipping lane users. The presence of turbines may affect fishing activities and navigational access, necessitating inclusive and participatory marine spatial planning. On the other hand, the provision of reliable electricity can improve the quality of life for coastal communities, open opportunities for small industry development, and support equitable development in remote areas. Meanwhile, from an environmental standpoint, the installation of tidal current turbines has a relatively lower impact compared to fossil fuel-based power plants, yet still requires thorough assessment. Potential impacts include changes in local current patterns, disturbances to marine biota habitats, and risks to fish and marine mammal migration. Additionally, bio fouling and structural deterioration can disrupt operations and necessitate the use of environmentally friendly materials and technologies. Therefore, a comprehensive environmental impact analysis and appropriate mitigation strategies are essential to ensure that tidal current energy development proceeds sustainably and in harmony with the conservation of Indonesia's marine ecosystems.
Keywords: Economy; Environment; Indonesian Strait; Renewable Energy; Society; Tidal turbines